Influence of Pier Settlement on Structural Stress of Longitudinal Connected Track in High-Speed Railways - Hui Fang (Advances in Civil Engineering)
Pier settlement is unavoidable in the construction and operation of high-speed railways. This paper presents a work on the influence of pier settlement on additional structural stress of longitudinal connected track (LCT). First of all, the generation mechanism of additional structural stress of LCT caused by pier settlement is described in detail. On this basis, the deformation of LCT caused by pier settlement is analytically deduced and a dynamic model of high-speed train-LCT-bridge coupled system considering pier settlement is established based on the train-track-bridge dynamic interaction theory, adopting which the additional structural stresses of LCT are discussed from static and dynamic perspectives. Results show that pier settlement has a great influence on the stability of LCT. Additional tensile stresses of LCT appear at settlement pier location and two adjacent pier locations. Tensile stresses on top surface of slab and on bottom surface of base should be paid attention to. The behaviors of LCT at adjacent pier locations cannot be ignored in studying the influence of pier settlement on the system. To ensure the stability of LCT and running performance of train, the control value of pier settlement is suggested to be 10.5 mm from the static and dynamic perspectives in practical engineering.